Strategi Komunikasi Organisasi Dalam Membangun Citra Universitas: Analisis Peran Hubungan Masyarakat di Era Digital - Nani Adismie Esti; Inatsa Thurfah Soerianda (Journal of Innovative and Creativity, 2026)
The development of the digital era has encouraged universities to manage organizational communication more strategically in order to build a positive institutional image. One unit that plays a crucial role in institutional communication is the Bureau of Academic and Student Administration (BAAK), which interacts directly with students as the university’s primary public. This study aims to analyze organizational communication strategies in building the image of Ibnu Chaldun University Jakarta through the role of Public Relations carried out by the Bureau of Academic and Student Administration in the digital era. This research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation. The results show that BAAK’s organizational communication strategies are implemented through the use of digital media, the structured delivery of academic information, and internal communication coordination with related units. However, there are still obstacles, including limited human resources and the suboptimal integration of digital communication strategies. This study is expected to contribute theoretically to the field of organizational communication and provide practical recommendations for communication management in higher education institutions.